2016
DOI: 10.1002/pon.4124
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of inequalities in psychosocial outcomes for women with breast cancer according to residential location and Indigenous status in Australia

Abstract: Background: The aim of this systematic review was to examine variations in psychosocial outcomes by residential location and Indigenous status in women diagnosed with breast cancer (BC) in Australia.Methods: Systematic searches were undertaken using multiple databases covering articles between 1 January 1990 and 1 March 2015 focusing on adult women with BC in an Australian setting and measuring quality of life (QOL), psychological distress or psychosocial support.Results: Thirteen quantitative and three qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 58 publications
0
28
0
2
Order By: Relevance
“…These characteristics were reflected in another review which explored the psychosocial outcomes for women with breast cancer. It showed that geographically isolated women had less access to information, services and continuity of care (Youl et al, ). The last review found some evidence towards greater survival for women with higher socioeconomic status; however, this was not conclusive (Lyle et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These characteristics were reflected in another review which explored the psychosocial outcomes for women with breast cancer. It showed that geographically isolated women had less access to information, services and continuity of care (Youl et al, ). The last review found some evidence towards greater survival for women with higher socioeconomic status; however, this was not conclusive (Lyle et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…There are several accepted factors which increase breast cancer recurrence and mortality which can be categorised into patient, tumour and treatment characteristics (Adami, Malker, Holmberg, Persson, & Stone, 1986;Carter, Allen, & Henson, 1989;Dasgupta et al, 2017;Fisher, Slack, & Bross, 1969;Joensuu et al, 2004;Koscielny et al, 1984;Li, Uribe, & Daling, 2005;Newman, 2009;Siegel, Miller, & Jemal, 2017;Tapia et al, 2017). These characteristics include patient age, ethnicity, tumour type, size, grade, stage, hormone receptor status, type of surgery and use of adjuvant therapies (Adami et al, 1986;Anders et al, 2008;Carter et al, 1989;Dasgupta et al, 2017;Fisher et al, 1969;Joensuu et al, 2004;Koscielny et al, 1984;Li et al, 2005;Newman, 2009;Siegel et al, 2017;Tapia et al, 2017;Youl et al, 2016).…”
mentioning
confidence: 99%
“…no. reviews contributing termsReviews contributing terms‘Place’Place of residence5No-5No-5[1014]‘Race’Race / ethnicity / culture / language3Yes →69No-9[11, 1522]Occupation6No-6No-6[11], [13], [16], [23], [24], [25]‘Gender’Gender / sex1Yes →67No-7[16], [17], [18], [19], [26], [27], [28]Religion0Yes →11Yes →23[17, 29, 30]Education7No-7No-7[11, 13, 16, 24, 25, 31, 32]‘SES’Socio-economic status12No-12No-12[11], [13], [15], [23], [24], [25], [31], [32], [33], [34], [35], [36]Social capital0Yes →11Yes →45[17, 3740]Other category not encompassed by PROGRESS-Plus6No-...…”
Section: Resultsmentioning
confidence: 99%
“…In 2017, it was estimated that 134,174 new cases would be diagnosed in Australia that will eventually lead to premature death and disability (Au et al, 2011;Australian Institute of Health & Welfare, 2017;Youl et al, 2016;Zucca, Boyes, Newling, Hall, & Girgis, 2011). In 2017, it was estimated that 134,174 new cases would be diagnosed in Australia that will eventually lead to premature death and disability (Au et al, 2011;Australian Institute of Health & Welfare, 2017;Youl et al, 2016;Zucca, Boyes, Newling, Hall, & Girgis, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…This assessment provides a direct measurement of the persons own perceptions of their need for help as well as the magnitude of their desire for help with those needs (Boyes, Girgis, & Lecathelinais, 2009). Cross-cultural and international comparisons of unmet supportive care needs have shown that different groups tend to prioritise different domains, for example, Japanese (Akechi et al, 2011) and Caucasian (Youl et al, 2016) women with breast cancer prioritise psychological needs while Chinese (Au et al, 2011) women prioritise information regarding health systems. Cross-cultural and international comparisons of unmet supportive care needs have shown that different groups tend to prioritise different domains, for example, Japanese (Akechi et al, 2011) and Caucasian (Youl et al, 2016) women with breast cancer prioritise psychological needs while Chinese (Au et al, 2011) women prioritise information regarding health systems.…”
Section: Introductionmentioning
confidence: 99%